Preparation and characterization of bio-adhesive Metformin Hydrochloride tablets (model drug) - الهوشي لمى; سليمان يوسف (Latakia University Journal -Medical Sciences Series, 2022)
The aim of this study was to prepare bio-adhesive tablets containing a model drug (eq. Metformin Hydrochloride) and to study the effect of bio-adhesive excipients on the properties of the prepared tablets. Matrix tablets were prepared by compression after wet granulation method using carbopol 940p, sodium alginate and croscarmellose sodium as bio-adhesive polymers. The properties of granules as flowbility and residual moisture and the properties of tablets (in terms of hardness, friability, weight uniformity, content uniformity, swelling index, ex vivo bio-adhesive time and strength and In vitro drug release) were evaluated. The results showed that the combination between carbopol 940p and sodium alginate (F3) achieved the longest bioadhesion time (˃9hrs) and longest drug release (11hrs). Drug release kinetics showed that drug release mechanism was to be zero order in most formulations. The results also showed that an increase of carbopol 940p amount led to an increase in bio-adhesion strength, bio-adhesion time and swelling index.